Value-Based Payment: What Does It Mean for Nurses?. Issue 3 (July 2021) - Pittman, Patricia; Rambur, Betty; Birch, Susan; Chan, Garrett K.; Cooke, Cindy; Cummins, Mollie; Leners, Colleen; Low, Lisa Kane; Meadows-Oliver, Mikki; Shattell, Mona; Taylor, Cheryl; Trautman, Deborah
Abstract : Among the many lessons that have been reinforced by the SARS-COVID-19 pandemic is the failure of our current fee-for-service health care system to either adequately respond to patient needs or offer financial sustainability. This has enhanced bipartisan interest in moving forward with value-based payment reforms. Nurses have a rich history of innovative care models that speak to their potential centrality in delivery system reforms. However, deficits in terms of educational preparation, and in some cases resistance, to considering cost alongside quality, has hindered the profession's contribution to the conversation about value-based payments and their implications for system change. Addressing this deficit will allow nurses to more fully engage in redesigning health care to better serve the physical, emotional, and economic well-being of this nation. It also has the potential to unleash nurses from the tethers of a fee-for-service system where they have been relegated to a labor cost and firmly locate nurses in a value-generating role. Nurse administrators and educators bear the responsibility for preparing nurses for this next chapter of nursing.